MOTIVASI BERWIRAUSAHA ANTARA PRIA DAN WANITA DI SURABAYA - Renita Sekar Ayu; Johny Rusdiyanto; Elsye Tandelilin (CALYPTRA, 2018)
This study aims to identify and analyze the differences in gender motivation of men and women entrepreneurship in Surabaya. The object is taken are men and women who entrepreneurship in Surabaya. The data used in this study is the primary data obtained from the distribution of questionnaires. Respondents in this study are 150 male and female respondents who have entrepreneurship at least 6 months. The sampling technique of this research is Purposive or Judgmental Sampling. This study uses a quantitative approach with research design is comparative. The test carried using T-test Independent Sample T and Partial Test with the help of Statistical Product and Service Solution (SPSS 23.00). The results of this study indicate that there is no difference in motivation Need for Affiliation, Need for Achievement, and Need for Power between men and women entrepreneurship in Surabaya. Each dimension of the motivation variable that is need for achivement, need for affiliation, and need for power shows every indicator of difference between men and women entrepreneurship in Surabaya.